Voxel-based morphometry reveals regional reductions of gray matter volume in school-aged children with short-term type 1 diabetes mellitus. Issue 7 (1st May 2019) - Liu, Kun; Huang, Xiaoyan; Cui, Shihan; Ye, Xinjian; Zhou, Yongjin; Song, Jiawen; Liu, Xiaozheng; Fu, Yuchuan; Shan, Xiaoou; Yan, Zhihan; Lin, Xiangtao
Abstract : Follow-up observation is needed for type 1 diabetes mellitus (T1DM) children due to the potential injury to the brain. However, the effect of short-term T1DM on gray matter in school-aged children is still unclear. This study aimed to evaluate gray matter volume (GMV) changes and their relationships with clinical variables in school-aged children with short-term T1DM. Twenty-one school-aged T1DM children were compared with 21 control patients, matched for sex and age. T1-weighted gradient echo three-dimensional MRI was performed using a 3.0-Tesla scanner and the resulting images were processed with FSL software to assess the difference in GMV between the two groups. The children with T1DM presented with decreased GMV in the left middle temporal gyrus (LMTG), the right postcentral gyrus, and the left triangular part of the frontal inferior gyrus (LTP-FIG). No significant changes in intelligence quotient (IQ) were found between the T1DM and control groups. In T1DM patients, there was a significant positive correlation between the GMV of LMTG and full-scale IQ or linguistic IQ. In addition, an increased glycosylated hemoglobin level was negatively correlated with reduced GMV in the LMTG and LTP-FIG in the T1DM group. These findings suggest that short-term T1DM could lead to regional structural brain deficits in school-aged children. The GMV of the LMTG may affect IQ, and poor recent glycemic control may have an adverse effect on GMV in the LMTG and LTP-FIG in T1DM children. Video abstract: http://links.lww.com/WNR/A506 Abstract : Supplemental Digital Content is available in the text.